The Impact of The 'Saudization' Policy on Indonesian Migrant Workers in Saudi Arabia - Hafizd Alharomain Lubis; Mohammad Izdiyan Muttaqin; Nurwahidin Nurwahidin (Green Publisher Indonesia, 2024)
This study aims to analyze the impact of the Saudization policy on Indonesian migrant workers in Saudi Arabia. Saudization is a Saudi government initiative that aims to increase local labor participation in the economy, reduce dependence on foreign labor, and is part of a broader effort designed under Vision 2030. This research uses qualitative methods through literature review and analysis of relevant government policies to assess how this policy affects employment opportunities, working conditions, and remittances sent by Indonesian migrant workers. The results show that Saudization has resulted in a significant decrease in employment opportunities for Indonesian migrant workers, with the construction sector experiencing a decrease in migrant worker acceptance of up to 20% and a 25% decrease in remittances to Indonesia. Working conditions for migrant workers remaining in Saudi Arabia have also deteriorated, including a 15% reduction in average wages. In response, migrant workers are adopting various adaptation strategies, including skills upgrading, diversification of migration destinations, and self-employment. The Indonesian government has increased diplomatic efforts to protect migrant workers, signed new agreements for worker protection, and promoted training to improve workers' skills. This study suggests that policies such as Saudization require a broader international coordination approach to ensure that national labor policies do not harm migrant workers and disrupt the global economy.